ANALISIS KOMPETENSI KEPALA TATA USAHA DALAM MENINGKATKAN PELAYANAN ADMINISTRASI AKADEMIK DI SMA NEGERI 10 BULUKUMBA - Amalia Ramdani Darap; Muh. Ardiansyah; Hasan, Hasan (Nusantara Hasana Journal, 2025)
This study aims to determine the implementation of academic administration services, evaluate the competence of the Head of Administration, and his/her contribution to improving services. The method used is descriptive qualitative with observation, interview, and documentation techniques. Data analysis through reduction, presentation, and drawing conclusions, as well as triangulation for data validity. The results show that the Head of Administration at SMA Negeri 10 Bulukumba has good competence in personality, social, technical, and managerial aspects, which contribute positively to the quality of academic services. The main obstacle is the use of information technology, but leadership support and internal coordination are the keys to the success of effective and efficient services.